2021
DOI: 10.1021/acs.jpclett.1c01436
|View full text |Cite
|
Sign up to set email alerts
|

Transient Near-UV Absorption of the Light-Driven Sodium Pump Krokinobacter eikastus Rhodopsin 2: A Spectroscopic Marker for Retinal Configuration

Abstract: We report a transient signature in the near-UV absorption of Krokinobacter eikastus rhodopsin 2 (KR2), which spans from the femtosecond up to the millisecond time scale. The signature rises with the all-trans to 13-cis isomerization of retinal and decays with the reisomerization to all-trans in the late photocycle, making it a promising marker band for retinal configuration. Hybrid quantum mechanics/molecular mechanics simulations show that the near-UV absorption signal corresponds to an S 0 → S 3 and/or an S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…After the extracellular release of the sodium ion, the protein converts back to the initial ground state. Based on mutation studies, spectroscopy and structural data, a number of residues besides the retinal Schiff base (RSB), N112, D116 and Q123 have been identified to be essential for ion uptake and release (1,6,11,12,(14)(15)(16)(17). The S64-Q123 pair seems to form an important gate blocking the Na + entry from the ground state into the ion pathway, which runs along helices B and C. The charged cluster E11-E160-R243 at the extracellular side is either part of the release pathway and/or important for protein stability (1,5,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…After the extracellular release of the sodium ion, the protein converts back to the initial ground state. Based on mutation studies, spectroscopy and structural data, a number of residues besides the retinal Schiff base (RSB), N112, D116 and Q123 have been identified to be essential for ion uptake and release (1,6,11,12,(14)(15)(16)(17). The S64-Q123 pair seems to form an important gate blocking the Na + entry from the ground state into the ion pathway, which runs along helices B and C. The charged cluster E11-E160-R243 at the extracellular side is either part of the release pathway and/or important for protein stability (1,5,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…This second bright state (SBS) of 13-cis retinal occurs with the formation of the hot J-intermediate and persists up to the decay of the M-intermediate, suggesting reisomerization occurring during the transition from M to O. 29 A slightly different view is given by recent photocycle studies on NaR and KR2, which show an equilibrium of two O-substates (O 1 and O 2 ) containing either 13-cis (O 1 ) or all-trans (O 2 ) retinal. 32,78,79 Here, the transition from O 1 to O 2 , and hence the isomerization step, is considered to be the molecular switch which leads to vectoriality of the sodium translocation.…”
Section: ■ Detailed View On the O-intermediatementioning
confidence: 99%
“…Ultrafast transient absorption experiments on a broad spectrum of microbial rhodopsins have shown that the excited state decay of retinal can often be described by a fast lifetime in the hundreds of fs range and by slower lifetimes which occur on the ps range. , The fast lifetime is usually assigned to the transition from the ES to the isomerized GS photoproduct via a conical intersection, whereas the nonreactive pathway is characterized by the slow lifetime components. As a result, two opposing models (and their variants) for the primary dynamics are mainly discussed in the broad community: The ES branching (Figure a) and the GS heterogeneity (Figure b) model. ,,, The surprisingly fast lifetime of around 200 fs in the case of KR2, combined with its structural uniqueness in the vicinity of the chromophore, revived the interest in this debate. Without a detailed look at those models and their nuances, which would be out of scope of this article, we explicitly focus on a few key aspects.…”
Section: Primary Photoreactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical spectroscopy:Rousso et al (1998);Kanehara et al (2017);Asido et al (2021) Vibrational spectroscopy:Garczarek and Gerwert, (2006);Lórenz-Fonfría and Kandori, (2009);Kraack et al (2011);Verhoefen et al (2011); Lórenz-Fonfría et al (2015a); Ito et al (2018); Watari et al (2019); Lórenz-Fonfría et al (2021) NMR/EPR spectroscopy: Smith et al (1989); Shi et al (2009); Mao et al (2014); Planchard et al (2014); Shigeta et al (2017); Mao et al (2019); Naito et al (2019); Friedrich et al (2020) Crystallography/EM: Havelka et al (1995); Kimura et al (1997); Belrhali et al (1999); Subramaniam et al (1999); Royant et al (2001); Vogeley et al (2004); Luecke et al (2008); Wada et al (2011); Kato et al (2012); Wang et al (2012); Frank et al (2014); Kato et al (2015); Nango et al (2016); Tsukamoto et al (2016); Broecker et al (2017); Hasegawa et al (2018); Ghanbarpour et al (2019); Kovalev et al (2019); Li et al (2019); Morizumi et al (2019); Shihoya et al (2019); Yun et al (2019); Besaw et al (2020); Hayashi et al (2020); Kovalev et al (2020a); Lu et al (2020); Bada Juarez et al (2021); Higuchi et al (2021); Li et al (2021); Suzuki et al (2022); Zhang et al (2022) Atomic force microscopy: Müller et al (2002); Klyszejko et al (2008); Yu et al (2017); Heath et al (2021) Computational: Hayashi et al (2001); Fujimoto et al (2007); Melaccio et al (2016); Karasuyama et al (2018); Tsujimura and Ishikita, (2020); Fujimoto, (2021); Shen et al (2021) Reviews: Béjà et al (2000); Caffrey, (2003); Engel and Gaub, (2008); Bamann et al (2014); Grote et al (2014); Neutze et al (2015); Engelhard et al (2018); Bibow, (2019); Kwon et al (2020); Kawasaki et al (2021) Solubilization: Yu et al (2000); Bayburt et al (2006); Yeh et al (2018); Ueta et al (2020) Other: Tribet et al (1996) Type-2 pigments Optical spectroscopy: Seki et al (1998); Salcedo et al (1999); Schafer and Farrens, (2015); Katayama et al (2019) Vibrational spectroscopy: Rothschild et al (1980); Kochendoerfer et al (1999) NMR/EPR spectroscopy: Creemers et al (1999); Carravetta et al (2004) Crystallography/EM: Sardet et al (1976); Davies et al (1996); Davies et al (2001); Krebs et al (2003); Standfuss et al (2007); Stenkamp, (2008); Hildebrand et al (2009); Blankenship et al (2015); García-Nafría and Tate, (2020); Zhang et al (2021a) Computational: Nikolaev et al (2018); Patel et al (2018) Reviews: Neitz and Neitz, (1998); Spudich et al (2000); Sakmar et al (2002); McDermott, (2009); Smith, (2010); Bickelmann et al (2015); Guo, (2020) Solubilization: Kropf, (1982); Sadaf et al (2015); Frauenfeld et al (2016); Lee et al (2020); Grime et al (2021)…”
mentioning
confidence: 99%